Legal Norms in the Focus of the Constructivism Theory - O. Khalabudenko (Теоретическая и прикладная юриспруденция)
The author, based on the theory of constructivism, explores the central concept of law — the legal norm. A consistent deconstruction of the legal norms is carried out, which allows us to distinguish three of its components: “Normative proposition” or “Normative utterance” about the rule of conduct, “Normative rule”, which serves as a model for assessing the behavior of a participant in legal communication in law enforcement, and “Rule of conduct” as the basis for the obligation of subjects of the legal communication. The proposed deconstruction allows, in the author’s opinion, to argue that the legislator who speaks out on the acceptable form of legally significant behavior is limited with legalization factors, the basis of which (the external border of the normative proposition) are moral imperatives. They define the boundaries of a person’s freedom and define the contours of his acceptable legal behavior. For a subject of law, a normative statement becomes imperative as a result of inclusion in legal communication. Such communication is possible only if there is a single code of legal communication. The aforementioned indicates the presence of structures of public consciousness (legal construction) that predetermine not only the choice of the form of behavior the participant in legal communication but also the characteristics of the normative statement itself. Law as an objective phenomenon, defined through the categories of truth or falsity, exists only at the level of normative utterance. In turn, normative rules and rules of conduct are evaluated through the criterion of effectiveness (achievement of a legal goal).The impossibility of deducing the true state of affairs from a rule that have a normative dimension allows us to assert that the components of the legal material that make up the content of any legal system have a constructive “nature”. According to the author, the methodology of legal constructivism removes the opposition between the norm and the legal relationship, making it meaningless to search in a normative matter for the actual content of acts of subjects of legal communication. The application of the approach under consideration allows us to state that the subject of legal communication is a way of representing the corresponding legal structure through his target behavior.